PENGARUH KEPUASAN KERJA KARYAWAN BAGIAN FRONTLINER DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH: Studi Kasus pada bank bjb Cabang Pangandaran - Nugraha, Heri; Afni Nurafiani (Program Studi Akuntansi IKOPIN, 2021)
In this study, the source of the company's competitive advantage actually comes fromthe employee's job satisfaction. It is more specifically stated by research by Homburgand Stock (2004) and Hassan et.al (2013) that job satisfaction that needs to beconsidered is the job satisfaction of frontliner employees. There are 37 frontlineremployees at bank bjb Pangandaran branch, namely 13 tellers, 3 customer service (CS)people and 21 security people. Meanwhile, customers with bank bjb Pangandaranbranches as of 31 December 2020 recorded 56,529 savings NOA, 777 current accountNOA, and 272 depositors. The basis of bank operations is trust, so that the bank is aninstitution that becomes a place for companies, government agencies and privateparties, as well as the public to save their funds or savings. Therefore, it is a start toimprove its services, considering the increasing mobility and needs. It aims to meetcustomer satisfaction as well as public trust, loyalty and loyalty to the banking world(Apriliani et al, 2014). Based on this explanation, it can be seen that in a competitionthat must be owned and carried out by the company is to increase the job satisfactionof frontliner employees and improve the quality of service so that it is expected that laterit will provide customer satisfaction.